Reconceptualization of Gala Agreement (Custom Pledge) in Aceh Society Based on Sharia - Azhari, Muhammad Iqbal, Adwani, Iman Jauhari (Opción, 1970)
The purpose of this research is to analyze and re-conceptualize the Gala agreement form on the Sharia-based customary law community in Aceh. This research is an empirical juridical research with a socio-legal approach. Utilization of collateral goods that has been practiced so far in the gala agreement, it is of course a mismatch of the use and control in the concept of Sharia pledge. Most of the scholars do not allow any utilization of gala objects in the absence of a time limit. Gala object utilization is permitted if the parties agree to implement the three contract of Gala agreement using the Al-Qardhul Hassan, Al-Mudharabah or Bai 'Al-Muqoyyadah agreements to avoid  the elements of scam (gharar) and usury (riba). One of the reconciliation forms in a sharia-based gala agreement is applying one of these contracts and the profits obtained from the gala object utilization by the pledgee (gala recipient) is used to recover the pledger’s (gala provider) debt.